2012
DOI: 10.1071/sh12076
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health and the Rugby World Cup 2011: a cross-sectional study of sexual health clinics in New Zealand

Abstract: These findings highlight issues that are amenable to prevention. The continued promotion of condoms as well as a reduction in the promotion and availability of alcohol at such events may reduce sexual health risks as well as other harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Seven per cent of women had non-consensual sex. 7 A study during the Vancouver Winter Olympic Games, did not show an increase in the supply of One other patient outside the time period analysed reported that he/she was in London to attend the Olympics Games.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Seven per cent of women had non-consensual sex. 7 A study during the Vancouver Winter Olympic Games, did not show an increase in the supply of One other patient outside the time period analysed reported that he/she was in London to attend the Olympics Games.…”
Section: Discussionmentioning
confidence: 89%
“…Seven per cent of women had non-consensual sex. 7 A study during the Vancouver Winter Olympic Games, did not show an increase in the supply of sex workers or trafficking, although it did show that a reduced number of clients were available during the time period. 8…”
Section: Discussionmentioning
confidence: 97%
“…Other norms at sporting mass gatherings may be associated with different kinds of risky behaviours, such as sexual risk-taking behaviours, that may increase the prevalence of health risks. For example, some rugby fans engage in consensual unprotected sex that might be associated with increasing the likelihood of sexually transmitted infections (STIs) [170].…”
Section: Norms That Emerge At Sporting Mass Gatherings Compatible Wit...mentioning
confidence: 99%